2016
DOI: 10.1016/j.ydbio.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Hormones in tomato leaf development

Abstract: Leaf development serves as a model for plant developmental flexibility. Flexible balancing of morphogenesis and differentiation during leaf development results in a large diversity of leaf forms, both between different species and within the same species. This diversity is particularly evident in compound leaves. Hormones are prominent regulators of leaf development. Here we discuss some of the roles of plant hormones and the cross-talk between different hormones in tomato compound-leaf development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 136 publications
1
68
0
Order By: Relevance
“…S2). It has previously been shown that the application of exogenous BA cannot mimic the effect of endogenous CKs on tomato leaf development (Fleishon et al , 2011; Shwartz et al , 2016). …”
Section: Resultsmentioning
confidence: 99%
“…S2). It has previously been shown that the application of exogenous BA cannot mimic the effect of endogenous CKs on tomato leaf development (Fleishon et al , 2011; Shwartz et al , 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, increasing expression of YUCCA genes (which have a pivotal role in the tryptophan-dependent auxin biosynthesis pathway; Hentrich et al, 2013) is correlated with increases in age and leaf complexity of the tree Gevuina avellane (Ostria-Gallardo et al, 2016). Cytokinins, such as zeatin, are important for leaf development, promoting morphogenesis during juvenile-to-adult transition (Shwartz et al, 2016). The effect of the cytokinin on leaf morphogenesis may be a result of its interaction with KNOTTED1-LIKE HOMEOBOX (KNOX1), as both are required for the regulation of leaf shape (Shani et al, 2009;Uchida et al, 2010;Bar and Ori, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…, 2009; Shwartz et al . , 2016). Furthermore, in M. truncatula , the MtPIN10‐generated local gradient of auxin activity functions differentially in lateral and terminal leaflet development (Zhou et al , 2011).…”
Section: Discussionmentioning
confidence: 99%